Evektifitas Media Big Book Terhadap Kemampuan Membaca Permulaan Anak Tunarungu Kelas Dasar IV di SLB Putra Mandiri Tarik Sidoarjo - Punasri Punasri (Universitas 45 Surabaya, 2023)
The research aims to determine the validity of the Big Book literacy media on the initial reading skills of deaf children in Elementary IV class at SDLB Putra Mandiri Tarik Sidoarjo. This research is classroom action research which aims to improve students' reading skills when studying Indonesian. The research subject was a deaf child in Elementary IV class at SDLB Putra Mandiri Tarik Sidoarjo. Initial reading ability tests and observation are the data collection methods used in this research. The implementation is carried out in 2 cycles which are carried out in 4 stages, namely planning, implementation, evaluation and reflection. Next, the data obtained was analyzed using qualitative analysis. The research results from cycle I, cycle II, cycle III and at the end of cycle IV showed that the use of big book media had a positive influence on the early reading abilities of deaf children.